(untitled) (Research, Society and Development, 2021)
Conventional cytology is a method created in 1928 for collecting cervical tissue as a preventive exam for cervical cancer, and even being the best method to do so then, it had flaws and a high rate of false-negatives. In 1991 Martha L. Hutchinson creates liquid-based cytology, technique that intended to mitigate this problems. This paper does an integrative literature review about conventional cytology and liquid-based cytology, comparing the advantages and disadvantages of each one of the analysis methods. The analyzed papers are journal articles, monographies, dissertations and thesis written in Portuguese between 2016 and 2021 that were found in scholar google, scientific electronic library online (Scielo), pubmed and scopus and had the keywords “citologia convencional”, “citologia em meio líquido”, “citologia convencional e citologia em meio líquido” or “citologia em meio líquido e citologia convencional”, being found five papers in the said parameters. It is concluded that liquid-based citology presents new potentialities to cytology, but the conventional one has a specific value in the simplicity of the method which requires no complex structures, making it efficient and trustworthy enough to justify it not being obsolete.